Dietary phytochemical approaches to stem cell regulation. (March 2020) - Zhang, Shuai; Lam, Kargo Kar Ho; Wan, Jack Hei; Yip, Chun Wang; Liu, Harry Kwun-Hung; Lau, Queenie Ming-Ngai; Man, Alice Hei-Yi; Cheung, Chun-Hei; Wong, Lik Hang; Chen, Hu Biao; Shi, Jun; Leung, George Par-Heng; et al.
Graphical abstract: Controlling proliferation and lineage differentiation of stem cells is critical for stem cell therapy in regenerative medicine. Phytochemicals such as phenols, flavonoids, sterols and alkaloids chemicals derived from food or herbs have obvious effects on modulating the self-renewal and function of stem cells, which are promising for the cooperative application with stem cells in various diseases. Highlights: Regulating stem cell fate is critical for regenerative medicine. Dietary phytochemicals modulate stem-cell fate via multiple signal pathways. Phytochemicals are promising for stem cell-based therapies. Abstract: Controlling self-renewal and lineage differentiation of stem cells (SCs) is critical for SC therapy in regenerative medicine. Multiple signal pathways such as Wnt, TGF-β and BMP are involved in modulating proliferation or specific differentiation of different types of SCs. Dietary phytochemicals, the major source of new drugs, are found to stimulate self-renewal and sub-population differentiation of SCs by activating/inhibiting the signal pathways (MAPK, canonical Wnt/β-catenin, AKT, etc.) and key transcription factors (OCT4, NANOG, Runx2, etc.). Dietary phytochemicals are important for SC therapy owing to the plethora of targets. In this review, we discussed the SC types and their regulatory mechanism. Applications of phenols, flavonoids, sterols and alkaloids chemicals from food or herbs on targeting SCs along with their molecular mechanisms are also discussed. Dietary phytochemicals are promising to enhance endogenous/exogenous SC therapy in various diseases.